Intravasation of SW620 colon cancer cell spheroids through the blood endothelial barrier is inhibited by clinical drugs and flavonoids in vitro. (January 2018) - Holzner, Silvio; Brenner, Stefan; Atanasov, Atanas Georgiev; Senfter, Daniel; Stadler, Serena; Nguyen, Chi Huu; Fristiohady, Adryan; Milovanovic, Daniela; Huttary, Nicole; Krieger, Sigurd; Bago-Horvath, Zsuzsanna; de Wever, Oliver; et al.
Abstract: Mechanisms how colorectal cancer (CRC) cells penetrate blood micro-vessel endothelia and metastasise is poorly understood. To study blood endothelial cell (BEC) barrier breaching by CRC emboli, an in vitro assay measuring BEC-free areas underneath SW620 cell spheroids, so called "circular chemorepellent induced defects" (CCIDs, appearing in consequence of endothelial retraction), was adapted and supported by Western blotting, EIA-, EROD- and luciferase reporter assays. Inhibition of ALOX12 or NF-κB in SW620 cells or BECs, respectively, caused attenuation of CCIDs. The FDA approved drugs vinpocetine [inhibiting ALOX12-dependent 12(S)-HETE synthesis], ketotifen [inhibiting NF-κB], carbamazepine and fenofibrate [inhibiting 12(S)-HETE and NF-κB] significantly attenuated CCID formation at low μM concentrations. In the 5-FU-resistant SW620-R/BEC model guanfacine, nifedipine and proadifen inhibited CCIDs stronger than in the naïve SW620/BEC model. This indicated that in SW620-R cells formerly silent (yet unidentified) genes became expressed and targetable by these drugs in course of resistance acquisition. Fenofibrate, and the flavonoids hispidulin and apigenin, which are present in medicinal plants, spices, herbs and fruits, attenuated CCID formation in both, naïve- and resistant models. As FDA-approved drugs and food-flavonoids inhibited established and acquired intravasative pathways and attenuated BEC barrier-breaching in vitro, this warrants testing of these compounds in CRC models in vivo . Highlights: SW620 colon cancer cell intravasation through the blood endothelial barrier correlates with ALOX12-or NF-kB activity. Clinical drugs which inhibit these activities attenuate blood endothelial barrier breaching in vitro . The flavonoids apigenin and hispidulin inhibit blood endothelial barrier breaching as well. Chemo-resistant colon cancer cells become targetable by clinical drugs which are inactive in naïve colon cancer cells.